2013
DOI: 10.1155/2013/305861
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 Protection against Liver Injury Produced by Various Hepatotoxicants

Abstract: To investigate the role of Nrf2 as a master defense against the hepatotoxicity produced by various chemicals, Nrf2-null, wild-type, Keap1-knock down (Keap1-Kd) and Keap1-hepatocyte knockout (Keap1-HKO) mice were used as a “graded Nrf2 activation” model. Mice were treated with 14 hepatotoxicants at appropriate doses, and blood and liver samples were collected thereafter (6 h to 7 days depending on the hepatotoxicant). Graded activation of Nrf2 offered a Nrf2-dependent protection against the hepatotoxicity produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 43 publications
(62 reference statements)
4
89
0
Order By: Relevance
“…Perturbations of ER homeostasis affect protein folding and cause ER stress [30]. ER stress is implicated in chemical-induced hepatotoxicity [31]. The results of the present study show that APAP administration causes severe ER stress in mice, demonstrated by remarkable elevations of hepatic GRP78, ATF-4, XBP-1s, and CHOP protein levels.…”
Section: Discussionmentioning
confidence: 52%
“…Perturbations of ER homeostasis affect protein folding and cause ER stress [30]. ER stress is implicated in chemical-induced hepatotoxicity [31]. The results of the present study show that APAP administration causes severe ER stress in mice, demonstrated by remarkable elevations of hepatic GRP78, ATF-4, XBP-1s, and CHOP protein levels.…”
Section: Discussionmentioning
confidence: 52%
“…In the comparison between the different derivatives, it was determined that both are potent inducers of HMOX1, which was confirmed by RT-PCR and Western blot; nevertheless, the results showed that CDDO-Im was a better inducer of the cytoprotective gene than CDDO-Me. Under oxidative stress conditions, HMOX1 expression is rapidly induced in most cell types, including HUVEC [5,48,49,50,51]. HMOX1 becomes the rate-limiting enzyme responsible for the initial step in the oxidative degradation of heme into biliverdin, iron, and carbon monoxide (CO) [52].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor E2-related factor 2 (Nrf2) is referred to as the ''master regulator'' of the antioxidant response via the antioxidant response elements (ARE), modulating the expression of hundreds of genes, including not only the familiar antioxidant enzymes, but large numbers of genes that control seemingly disparate processes such as immune and inflammatory responses, tissue remodelling and fibrosis, carcinogenesis and metastasis, and even cognitive dysfunction and addictive behavior [7][8][9]. Many researches have demonstrated that Nrf2 prevents the liver from many hepatotoxicants.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have demonstrated that Nrf2 prevents the liver from many hepatotoxicants. The Nrf2-mediated protection is accompanied by induction of antioxidant genes, suppression of inflammatory responses, inhibition of apoptosis and attenuation of oxidative stress [7,8,10].…”
Section: Introductionmentioning
confidence: 99%